investor sentiment and mutual fund performance - Zhang, Xiyue (2022)
Investor sentiment, reflecting investors' expectations of the market, is closely related to investors' trading behavior. This paper focuses on the impact of market investor sentiment on risk excess returns of 4288 mutual funds. We found that when investor sentiment rises, profit-oriented funds are more sensitive to investor sentiment, while profit-oriented funds obtain lower risk excess returns. At the same time, loss-making mutual funds obtain significantly higher alphas when investor sentiment rises. High sentiment sensitivity mutual funds invest more in small stocks. We also find that when investor sentiment is extremely high, there will be many noise traders, and the impact of sentiment on fund excess returns is not significant. But during periods of extremely low investor sentiment, increased sentiment has a differential impact on mutual fund wins and losses, resulting in lower alphas for winners and higher alphas for losers. At the same time, skilled mutual fund managers have the ability to exploit investor sentiment to generate excess returns. This paper uses AAII investor sentiment as a robustness test indicator and finds that AAII sentiment indicator and BW investor sentiment indicator have highly consistent effects on mutual fund excess returns.